Persepsi Masyarakat Terhadap Berbagai Lansekap Penggunaan Lahan Di Sekitar Tahura Bukit Barisan (Studi Kasus: Desa Semangat Gunung Dan Desa Merdeka Kecamatan Merdeka Kabupaten Karo) - Elisa M Hutabarat; Oding Affandi; Liliek P Asmono (Peronema Forestry Science Journal, 2012)
ELISA M HUTABARAT: Public Perception Of Various Land Use Landscape Around Tahura Bukit Barisan (Case study: Semangat Gunung Merdeka Village, Merdeka sub-distric, Karo District), guided by ODING AFFANDI and LILIEK P ASMONO. Public Perception Of Various Land Use Landscape Forest is considered very important because of forests have a positive impact on the forest communities economy.. However, the lack of equality between the roles of men and women in perceiving the importance of  forest in Semangat Gunung and Merdeka village associated with different land uses appropriate level of needs. Data collection techniques  was done by using MLA (Multidisciplinary Assessment landcape). Research showed  that  women’s perception is higher than men's perceptions in Semangat Gunung Village on assesment of forest land.  Instead men’s perception is higher than women's perceptions on assessment of forest land in Merdeka Village. Keywords: Perceptions, Tahura Bukit Barisan, Landscape, MLA